Crime and Networks: 10 Policy Lessons - Matthew J. Lindquist; Yves Zenou (Institute of Labor Economics (IZA), 2019)
Social network analysis can help us understand more about the root causes of delinquent behavior and crime and provide practical guidance for the design of crime prevention policies. To illustrate these points, we first present a selective review of several key studies and findings from the criminology and police studies literature. We then turn to a presentation of recent contributions made by network economists. We highlight 10 policy lessons and provide a discussion of recent developments in the use of big data and computer technology.
Keywords: A14; K42; Z13; 330; co-offending; crime; criminal networks; social networks; peer effects; key player